The experience of polyethylene glycol (PEG) bowel preparation in adolescents undergoing colonoscopy - Örmon, Karin (BMC Res Notes, 2020)
OBJECTIVE: The aim of this study was to describe the experience of polyethylene glycol (PEG) bowel preparation in adolescents undergoing colonoscopy. RESULTS: 32 adolescents, 10–18 years of age self-reported a minimum of complications 1 week after colonoscopy when PEG was used for bowel preparation. 17 adolescents, 10–18 years were also interviewed about bowel preparation with PEG. Using qualitative content analysis, two categories were extracted from the data: “Being decisive makes it manageable” and “Be prepared for a horrible experience.” The adolescents reported PEG intake difficulty; the intake was, however, manageable if they received appropriate information.